THERAPEUTIC DRUG MONITORING OF ANTICONVULSANTS IN CLINICAL PRACTICS - Yu. B. Belousov; M. V. Leonova; L. L. Shteinberg; I. F. Tischenkova; A. V. Sokolov (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: his paper presents the results of therapeutic drug monitoring (TDM) of anticonvulsants (valproats and carbamazepins) in 614 patients with epilepsy in clinical practices. 295 patients were treated with different drugs of valproats and 314 patients were treated with different drugs of carbamazepine. The frequency of achievement the therapeutic concentrations on valproat treatment was 66,4%, the average daily dose was 1325,1 mg. The frequency of achievement the therapeutic concentrations on treatment with drug forms with prolong release (Depakin chrono, Convulex retard) was higher, than on drug forms with immediate release. The frequency of subtherapeutic concentrations on valproat treatment was 16,3% and overtherapeutic concentrations – 1%. In doses of valproats less then 500 mg there was no patients with therapeutic concentrations, in doses 1001-1500 mg/day the therapeutic concentrations have 75% patients, in doses higher than 2000 mg/day – there was a risk of overdose. The frequency of achievement the therapeutic concentrations on carbamazepine treatment was 78,6%, the average daily dose was 922,2 mg. The frequency of achievement the therapeutic concentrations on treatment with drug forms with prolong release (Tedretol CR, Finlepsin retard) was higher, than on drug forms with immediate release. The frequency of subtherapeutic concentrations on carbamazepine treatment was 6,3% and overtherapeutic concentrations – 1,25%. When used initial daily doses (less then 600 mg) 64,3% patients have therapeutic concentrations , when used highly doses (high than 600 mg) 87% patients have therapeutic concentrations. In daily doses of carbamazepine higher then 600 mg and 1200 mg the frequency of the overtherapeutic concentrations were 1,3% and 4,1% both by Cmin and Cmax, only by overtherapeutic Cmax – 8,8% and 18,4%.